If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(y+2)=-4(5y-1)+7y
We move all terms to the left:
5(y+2)-(-4(5y-1)+7y)=0
We multiply parentheses
5y-(-4(5y-1)+7y)+10=0
We calculate terms in parentheses: -(-4(5y-1)+7y), so:We get rid of parentheses
-4(5y-1)+7y
We add all the numbers together, and all the variables
7y-4(5y-1)
We multiply parentheses
7y-20y+4
We add all the numbers together, and all the variables
-13y+4
Back to the equation:
-(-13y+4)
5y+13y-4+10=0
We add all the numbers together, and all the variables
18y+6=0
We move all terms containing y to the left, all other terms to the right
18y=-6
y=-6/18
y=-1/3
| u+4.88=9.66 | | g/4+5=8 | | (10x-1)+(15x+7)+(18x+2)=180 | | 15u+19u-6u+13u=14 | | -3/5v=6 | | -7+4(5n+7)=19 | | 15u+19u–6u+13u=14 | | (10x-1)+(15x+7)=180 | | 7.5x=48.75 | | 248=197-x | | -3.8-(-1-9.7x)=2.6+13.3x | | 19q–14q=5 | | 7=15x-8 | | 2w-2=20 | | 5x+1+2x+2x+2=84 | | -15u+-19u–6u+3u+20u=14 | | 17x=36 | | x2+20x=0 | | 4a-20=а+4 | | 3(2x-1)-4(x+2#0=0 | | 5x+3+5x+3+4x+1+4x+1=134 | | 14=-4v+2(v+4) | | 7x+8=4x-16 | | 9x+9x=6x+12 | | 5x+3+5x+3=4x+1+4x+1 | | 9v=517 | | X+2b+3b=180 | | 12/4=30/b | | v-1=7 | | 4(6+x)=4(6)+4(3) | | 13=-4/n | | t+2/4=8/1 |